Inset Mapper: A software tool in Island cartography - Papakonstantinou, Apostolos; Varsamis, Dimitris; Soulakellis, Nikolaos (My University, 2013)
Island cartography deals with special cartographic problems confronted in the portrayal of island regions and demands the use of specially developed software tools. One of the most commonly faced problems is the need of inset map creation for very small islands, and sometimes isolated ones, that must be displayed in the main map. This paper presents the methodology followed for the development of the Inset Mapper (IM) Software toolbox, describes the toolbox, and showcases its ability to create inset maps in Island regions. The IM software tool provides a useful cartographic tool for assisting the selection of the most appropriate position and scale of the inset map in an Island region.
Keywords: Island cartography; Inset maps; Scale selection; Geovisualization